2015
DOI: 10.1093/ntr/ntu248
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Responses to Cues Presented in the Natural Environment of Cigarette Smokers

Abstract: IntroductionMost quit attempts end in relapse, 1 and there is evidence that female smokers have more difficulty quitting smoking than male smokers. [2][3][4] This gender difference has often been observed in clinical trials, 5,6 but population-based evidence for gender differences in quit success has been mixed. 7,8 An appeal for research identifying mechanisms related to these disparate cessation outcomes has been made in the smoking literature. 9 Craving, stress, and negative affect (NA) have been hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 35 publications
5
41
0
2
Order By: Relevance
“…This pattern may be related to gender differences in nicotine motivation. Women smokers appear to differ from men smokers in: nicotine reinforcement (Perkins et al, 1999), sensitivity to the nicotine content of cigarettes as reflected by withdrawal alleviation (Perkins & Karelitz, 2015), sensitivity to stressors, smoking cues, and abstinence as manifested in increased smoking motivation (Perkins, et al, 2013; Doran, 2014; Wray et al, 2015; although cf. Ferguson, et al, 2015); and negative reinforcement expectancies for smoking (Ferguson, Shiffman, & Gwaltney, 2006; Pang, et al, 2015; Perkins et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern may be related to gender differences in nicotine motivation. Women smokers appear to differ from men smokers in: nicotine reinforcement (Perkins et al, 1999), sensitivity to the nicotine content of cigarettes as reflected by withdrawal alleviation (Perkins & Karelitz, 2015), sensitivity to stressors, smoking cues, and abstinence as manifested in increased smoking motivation (Perkins, et al, 2013; Doran, 2014; Wray et al, 2015; although cf. Ferguson, et al, 2015); and negative reinforcement expectancies for smoking (Ferguson, Shiffman, & Gwaltney, 2006; Pang, et al, 2015; Perkins et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We were interested in whether DUs 1) smoke fewer cigarettes and have lower carbon monoxide (CO) levels than SOs; 2) show elevated levels of nicotine relative to SOs, especially during periods of smoking reduction when they could use e-cigarettes ad libitum; 3) report lower levels of withdrawal symptoms during periods of smoking reduction; and 4) are more able than SOs to reduce and/or stop their cigarette use. We sought to determine whether any observed differences between DUs and SOs were related to gender and nicotine dependence, factors implicated in smoking motivation and cessation success (Perkins, Donny, & Caggiula, 1999; Piper, McCarthy, et al, 2008; Wray et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…There are gender differences in reactivity to cues; for example, females express greater craving in response to smoking-related cues when compared to men (Knott et al, 2008;Tong, Bovbjerg, & Erblich, 2007). Previous research has also found that females show higher sensitivity than males to negative emotional cues (Carpenter et al, 2014;Colamussi, Bovbjerg, & Erblich, 2007;Saladin et al, 2012;Wray et al, 2015). There are other factors that have been related to greater craving for cigarettes, including younger age, higher nicotine dependence and symptoms of anxiety (García-Rodríguez et al, 2011;Sayette, Martin, Wertz, Shiffman, & Perrott, 2001;ThompsonLake et al, 2014;Watson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The current study combined EMA-based methods with a novel cue-reactivity paradigm (cue reactivity ecological momentary assessment, CREMA; Warthen and Tiffany 2009; Wray et al 2011; Wray et al 2015) in which pictorial cues are administered via an electronic device to participants in their natural environments in conjunction with EMA-based assessments. Our goal was to examine associations between alcohol consumption, tonic (non-cue-elicited) cigarette craving, and responses to smoking and stress cues presented in the natural environment of adult smokers via CREMA.…”
mentioning
confidence: 99%